A Victimological Analysis on Acid Throwing Attack (With a View to the Case of Ameneh Bahrami Navaa) - Mehrdad Rayejian Asli (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2013)
Acid Throwing attack is a terrible violent crime against the person whichis not properly analyzed in criminal law, nor in criminology. Globalstatistics, if they are not of concern to international community, affirm thenecessity of finding a solution for this problem. One of the most importantaspects to explore the phenomenon is the issue of acid violence victimswhich requires a special consideration in theory and practice. Meanwhile,Ameneh Bahrami Navaa Case has significant points from the victimologicalperspective. The case shows that the Iranian society, as well as its legalsystem, face serious defects to protect victims of acid violence. Thenecessity of remedy of moral damage, providing and imposing proportionatepenalties, prevention of acid throwing attacks and control of its increasingrate all are of issues which have a need of consideration.